IJCM_289A: Determination of factors favouring the snake bite mortality in Himachal Pradesh - Gandhi Manoj Kumar; Chauhan Nidhi; Raina Sunil K (Wolters Kluwer Medknow Publications, 2024)
Background: Snake bite is an established important cause of morbidity and mortality among the poor and rural population across the world including India. India accounts for the highest number of snakebites and related mortality globally. Objective: Identification of factors favoring the mortality due to snake bite. Methodology: A descriptive cross-sectional study was conducted from April 2022 to March 2023, and deaths due to snake bites reported from different health care facilities and community were included in the study. Results: A case-fatality rate of 5.9% due to snake bite was documented in the study. The factors identified as favorable for mortality were delayed treatment, followed by suboptimal care at primary and secondary health care facilities and traditional beliefs of the community. Conclusion: Provision of emergency service as point of care delivery, focusing on provision of training to strength point of care emergency services, co-ordination and linkages with the community members can strengthen the efforts toward reducing the mortality due to snake bites.